Acute Recreational Noise-Induced Cochlear Synaptic Dysfunction in Humans With Normal Hearing: A Prospective Cohort Study - Wang, Qixuan; Yang, Lu; Qian, Minfei; Hong, Yingying; Wang, Xueling; Huang, Zhiwu; Wu, Hao (Frontiers in Neuroscience, 2021)
Objectives: To identify the acute high-intensity recreational noise-induced effects on auditory function, especially the cochlear synaptopathy-related audiological metrics, in humans with normal hearing. Methods: This prospective cohort study enrolled 32 young adults (14 males and 18 females), the mean age was 24.1 ± 2.4 years (ranged from 20 to 29). All participants with normal hearing (audiometric thresholds ≤ 25 dB HL at frequencies 0.25, 0.5, 1, 2, 3, 4, 6 and 8 kHz for both ears) had already decided to participate in the outdoor music festival. Participants were asked to measure the noise exposure dose and complete auditory examinations, including the air-conduction pure-tone audiometry (PTA), distortion product otoacoustic emission (DPOAE), contralateral suppression (CS) on transient evoked otoacoustic emission (TEOAE), auditory brainstem response (ABR) test and Mandarin Hearing in Noise Test (MHINT), at baseline and one day and 14 days after music festival noise exposure. Results: The mean time of attending the music festival was 7.34 ± 0.63 hours (ranged from 6.4 to 9.5), the mean time-weighted average (TWA) of noise exposure dose was 93.2 ± 2.39 dB (A) (ranged from 87.9 to 97.7). At neither one day nor 14 days post exposure, there were no statistically significant effects on PTA thresholds, DPOAE amplitudes, CS on TEOAEs or MHINT signal-to-noise ratios (SNRs) of acute outdoor music festival noise exposure, regardless of sex. While the ABR wave I amplitudes significantly decreased at one day after exposure and recovered at 14 days after exposure, the exposed/unexposed ABR wave I amplitude ratio was significantly correlated with MHINT SNR change at one day after exposure, although it was not correlated with the noise exposure dose. Conclusions: In young adults with normal hearing, we found the self-compared decrement of ABR wave I amplitudes at one day post the acute recreational noise exposure at high intensity, which also contribute to the change of speech perceptual ability in noisy backgrounds. This study indicated that auditory electrophysiological metric changes might be a more sensitive and efficient indicator of noise-induced cochlear synaptic dysfunction in humans. More attention should be paid to the recreational noise-induced cochlear synaptopathy and auditory perceptual disorder.